2010
DOI: 10.1111/j.1399-0012.2009.01194.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and new onset diabetes after transplantation in kidney transplant recipients

Abstract: Background Metabolic syndrome (MS) and new onset diabetes after transplant (NODAT) are common in kidney transplant patients. We studied the relationship between the two conditions and their impact on metabolic and cardiovascular risk profiles. Methods All non-diabetic patients transplanted between 1999 and 2005 who were followed up to 2006 were included. MS and NODAT were determined. Kaplan–Meier survival and various regression analyses were performed to determine the clinical correlates for both conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…Recently published studies carried out in renal transplant recipients reported NODAT as a common condition, with incidences ranging from 13.0%–46.3% over 5 years posttransplant 2325. These studies also supported the association between the presence of metabolic syndrome either after renal transplant23,24 or within the month prior to transplant25 and the development of NODAT, with increased risks of 3.5 and 1.3, respectively 23,25…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Recently published studies carried out in renal transplant recipients reported NODAT as a common condition, with incidences ranging from 13.0%–46.3% over 5 years posttransplant 2325. These studies also supported the association between the presence of metabolic syndrome either after renal transplant23,24 or within the month prior to transplant25 and the development of NODAT, with increased risks of 3.5 and 1.3, respectively 23,25…”
Section: Discussionmentioning
confidence: 52%
“…Even though some of these factors also define metabolic syndrome, the specific role of metabolic syndrome in the development of diabetes has not been completely clarified yet. However, three recently published studies have shed some light on this matter, showing that diagnosis of metabolic syndrome after renal transplant23,24 and within the month prior to transplant25 was associated with an increased risk of NODAT.…”
Section: Introductionmentioning
confidence: 99%
“…Last, the effect of insulin treatment on the metabolic syndrome should be examined; this common complication after renal transplantation is associated with cardiovascular risk profiles. 37,38 In summary, our study shows that evening hyperglycemia (glucose level $200 mg/dl) is the rule, not the exception, after renal transplantation and that early basal insulin is effective in reducing HbA1c and decreasing NODAT over the long term (presumably by improving b-cell function). This promising evidence in favor of early basal insulin therapy after transplantation needs to be addressed in larger clinical trials.…”
Section: Discussionmentioning
confidence: 62%
“…Blood has been shown to be a reservoir of CD11c+ MHC II+ DCs and CD11c+ MHC II– putative precursor population [30,31,32]. We had demonstrated earlier that, in response to peripheral SEA challenge, the number of conventional (all DCs except plasmacytoid DCs) and plasmacytoid DCs increased in the spleen, PLN and MLN by 24 h [22], and this increase was not the result of DCs replicating in situ (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…2b) suggesting that the expression levels were slightly over background staining. Thus, SEA induced accumulation of lung CD11c+ cells with a first wave resulting in an increase in the percentage and number of CD11c+ MHC II+ DCs at 24 h, followed by a second wave resulting in an increase in the CD11c+ MHC II– cell population at 48 h. This CD11c+ MHC II– cell population could potentially be a progenitor for different immune cell types, and cells with a similar phenotype have been described by other groups as a putative immediate DC precursor population [29,30,31,32]. …”
Section: Resultsmentioning
confidence: 99%